Dietary Iron Restriction Improves Muscle Function, Dyslipidemia, and Decreased Muscle Oxidative Stress in Streptozotocin-Induced Diabetic Rats - Manuel Alejandro Vargas-Vargas; Alfredo Saavedra-Molina; Mariana Gómez-Barroso; Donovan Peña-Montes; Christian Cortés-Rojo; Huerta Miguel; Xochitl Trujillo; Rocío Montoya-Pérez (MDPI AG, 2022)
Diabetes mellitus is a chronic degenerative disease characterized by hyperglycemia and oxidative stress. Iron catalyzes free radical overproduction. High iron concentrations have previously been reported to promote an increase in oxidative stress; however, the effect of iron restriction in diabetes has not yet been explored, so we tested to see if iron restriction in diabetic rats reduces oxidative damage and improved muscle function. Wistar rats were assigned to 4 groups: Control; Diabetic; Diabetic rats with a high iron diet, and Diabetic with dietary iron restriction. After 8 weeks the rats were sacrificed, the muscles were extracted to prepare homogenates, and serum was obtained for biochemical measurements. Low iron diabetic rats showed an increase in the development of muscle strength in both muscles. Dietary iron restriction decreased triglyceride concentrations compared to the untreated diabetic rats and the levels of extremely low-density lipoproteins. Aggravation of lipid peroxidation was observed in the diabetic group with a high iron diet, while these levels remained low with iron restriction. Iron restriction improved muscle strength development and reduced fatigue times; this was related to better lipid profile control and decreased oxidant stress markers.